2023
DOI: 10.1039/d3bm00030c
|View full text |Cite
|
Sign up to set email alerts
|

Zn–Sr-sintered true bone ceramics enhance bone repair and regeneration

Abstract: Bone defects are one of the toughest challenges faced by orthopedic surgeons worldwide, especially at critical sizes, which are caused by severe trauma, malignancy, or congenital disease. The ideal bone...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It has been demonstrated that the presence of Zn enhances osteogenic differentiation, bone formation, and mineralization. Additionally, according to the literature, zinc stimulates the formation and mineralization of osteoblastic bone by activating aminoacyl‐tRNA synthetase, 40 which is the rate‐limiting enzyme in the protein synthesis translation process within cells, and directly stimulates cellular protein synthesis. Further, zinc particles have significant antibacterial potential.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the presence of Zn enhances osteogenic differentiation, bone formation, and mineralization. Additionally, according to the literature, zinc stimulates the formation and mineralization of osteoblastic bone by activating aminoacyl‐tRNA synthetase, 40 which is the rate‐limiting enzyme in the protein synthesis translation process within cells, and directly stimulates cellular protein synthesis. Further, zinc particles have significant antibacterial potential.…”
Section: Resultsmentioning
confidence: 99%
“…Zn–Sr sintered TCP exhibited good osteogenic and antibacterial properties in vitro , as well as good osteointegration and bone growth in vivo . 196 TCP doped with Zn, Si, and Sr elements exhibited better angiogenic ability. 118 Therefore, Zn incorporation is a promising method to improve osteogenic, antibacterial, angiogenic, immunomodulatory, and mechanical properties of TCP.…”
Section: Application Of Zinc-based Biomaterials In Bone Repair and Re...mentioning
confidence: 95%
“…While excessive strontium can induce apoptosis, 121,122 it is typically incorporated in low concentrations as an osteoinductive element, often synergistically with other ions like zinc, silver, and magnesium, to bolster angiogenesis and osteogenesis. [123][124][125] F I G U R E 5 (A) Representative H&E images of the bone defect 7, 14, and 28 days after applying GBR membranes (Col, Col-MgO200, and Col-MgO500). The asterisks represent membranes, WB stands for Woven Bone.…”
Section: Strontiummentioning
confidence: 99%